Breast cancer screening behaviors among Chinese women in Mainland China. (19th June 2018) - Bao, Yingyi; Kwok, Cannas; Lee, Chun Fan
Abstract: In the present study, we reported on the current breast cancer screening rates among Chinese women in China and examined whether demographic factors and cultural beliefs were associated with their screening behavior. A cross‐sectional survey was conducted with a convenience sample of 494 Chinese women who completed the modified Breast Cancer Screening Beliefs Questionnaire (BCSBQ). Two‐sample t ‐tests and multivariable logistic regression were employed to analyze the data. The results indicated that participation in screening practices ranged from 27.5% for breast self‐examination (BSE), 36.4% for clinical breast examination, 23.5% for mammography, and 40% for ultrasonography. Women who had previously engaged in one of the four screening practices had significantly higher scores on the three subscales of the modified BCSBQ. Being older and having a friend who had been diagnosed with breast cancer were shown to be predictors for BSE and participation in either mammography or ultrasonography, respectively. Education levels were also shown to be positively associated with the four screening measures. We suggest that cultural beliefs about breast cancer and screening practices play a significant role in Chinese women's screening behavior.